Pedagogika moralna Immanuela Kanta jako wyraz wychowania do odpowiedzialności - Nowicka, Anna (Biuletyn Historii Wychowania, 2010)
The author discusses I. Kant’s pedagogical views and beliefs related to moral education. In particular, the author attempts to prove the thesis that, for Kant, all education and proper upbringing was ultimately linked with moral education and that moral education, in turn, was just education to responsibility. After a presentation of the main assumptions of Immanuel Kant’s ethics, the author proceeds to discuss the status of pedagogy within its framework as a science that aims at educating people and forms attitudes that were understood to involve meeting of one’s obligations expressed in the formula of the categorical imperative, and precisely based on making one to the influence of a priori moral principles and on practicing skills of making everyday use of them in different life situations. The author characterizes notions that are related in Kant’s philosophy to the problems of prospective and positive moral responsibility, and discusses how this philosophy responds to the problem of feasibility and ways of developing a responsible attitude in man. Further on, the author discusses in detail Kant’s pedagogy, i.e. attempts to discover the connective concepts necessary to understand how Kant perceived the educational reality within the context of responsibility, attempts to answer what its goal and essence are and what measures are to be taken to successfully achieve the goal. The considerations on the notion of responsibility and pedagogy in Kant’s thought are summarized in a brief presentation of its essential significance for the pedagogy of morality.